Optimizing Growth and Bioactive Compound Production in Split Gill Mushroom (Schizophyllum commune) Using Methyl Jasmonate - Preuk Chutimanukul; Siripong Sukdee; Kittichai Boonmee; Ornprapa Thepsilvisut; Onmanee Prajuabjinda; Ubonwan Saesiw; Pattama Sriumpai; Hiroshi Ehara (Resources, 2024)
The split gill mushroom (Schizophyllum commune) is a valuable natural resource with high nutritional value and diverse bioactive metabolites, underscoring its potential for sustainable applications. By applying elicitors, this study highlights the quality enhancement of S. commune fruiting bodies, a commercially significant resource. While elicitors have been shown to stimulate beneficial bioactive compound production, research on their use in S. commune remains limited. This study applied methyl jasmonate (MeJA) at various concentrations (0, 4, 13, 22, 31, and 40 µM) to optimize growth, improve nutritional value, promote triterpenoid and phenolic compound synthesis, and boost antioxidant activity in S. commune. The results demonstrated that MeJA’s effects on growth and bioactive compounds are concentration-dependent. A concentration of 22 µM was identified as the most effective, resulting in the highest growth performance, including cap diameter (2.01 cm), fresh weight (24.10 g), and biological efficiency (15.21%). Furthermore, all MeJA treatments significantly enhanced triterpenoid, phenolic compound, and antioxidant activity compared to the control. These findings present a promising approach to enhance the sustainable use of S. commune as a natural resource by improving its quality and bioactive properties. Additionally, this research contributes to understanding the role of MeJA in promoting the growth and production of bioactive compounds in mushrooms, offering insights for advancing mushroom-based natural resource management.